A Comparative Study of Iterative Solvers Exploiting Spectral Information for SPD Systems - Giraud, Luc; Ruiz, Daniel; Touhami, Ahmed (SIAM journal on scientific computing, 2006)
When solving the symmetric positive definite (SPD) linear system ${\bf A} {\bf x}^\star = {\bf b}$ with the conjugate gradient method, the smallest eigenvalues in the matrix ${\bf A}$ often slow down the convergence. Consequently if the smallest eigenvalues in ${\bf A}$ could somehow be "removed," the convergence may be improved. This observation is of importance even when a preconditioner is used, and some extra techniques might be investigated to further improve the convergence rate of the conjugate gradient on the given preconditioned system. Several techniques have been proposed in the literature that consist of either updating the preconditioner or enforcing conjugate gradient to work in the orthogonal complement of an invariant subspace associated with the smallest eigenvalues. The goal of this work is to compare several of these techniques in terms of numerical efficiency. Among various possibilities, we exploit the Partial Spectral Factorization algorithm presented in [M. Arioli and D. Ruiz, Technical Report RAL-TR-2002-021, Rutherford Appleton Laboratory, Atlas Center, Didcot, Oxfordshire, England, 2002] to compute an orthonormal basis of a near-invariant subspace of ${\bf A}$ associated with the smallest eigenvalues. This eigeninformation is used in combination with different solution techniques. In particular we consider the deflated version of conjugategradient. As representative of techniques exploiting the spectral information to update the preconditioner we consider also the approaches that attempt to shift the smallest eigenvalues close to one where most of the eigenvalues of the preconditioned matrix should be located. Finally, we consider an algebraic two-grid scheme inspired by ideas from the multigrid philosophy. In this paper, we describe these various variants and we compare their numerical behavior on a set of model problems from Matrix Market or arising from the discretization via the finite element technique of some two-dimensional (2D) heterogeneous diffusion PDE problems. We discuss their numerical efficiency, computational complexity, and sensitivity to the accuracy of the eigencalculation.